GEORADAR ASPECTS OF SECURITY OF NEAR-SURFACE CRITICAL INFRASTRUCTURE FACILITIES - Tarasenko, Yu. S.; Savchenko, Iu. V. (Systems and Technologies, 2023)
A significant part of the existing technosphere of the society refers to critical infrastructure objects, which are obliged to apply modern security and cybersecurity systems with a potentially high level of their realization. The article presents the material devoted to the georadiolocation capabilities of near-surface ground diagnostics from the position of ensuring the safety of underground engineering structures. However, when ensuring such safety by means of georadiolocation, it is difficult to get rid of the high level of ambiguity of interpretation of the obtained data on deep inhomogeneities. It is noted that, even at a priori low level of reliability of the results of conducted studies by means of georadiolocation, they are mostly of qualitative nature due to poor predictability of the heterogeneous nature of the near-surface layers of the earth. In this connection, from the point of view of modelling hypothetical measurements, first of all concerning the receiving and transmitting horn antenna unit, the cognitive method of “black box” was used. Being oriented on ITU-R Recommendations (series P, Radio Wave Propagation) concerning electrical characteristics of the earth surface, it is proposed to replace the parameters of the real environment by its effective values, but for homogeneous soil. In accordance with what impedance parameters of electrical characteristics of the soil are introduced and aspects of matching the antenna system with the probed medium by effective values of its (soil) electrical characteristics are considered, the implementation of which provides an increase in the probabilistic level of diagnostics of the layered inhomogeneous earth surface. The described aspects of the near-surface diagnostics of the Earth by means of electromagnetic deep sounding with a variable set of “lenses of clarified optics”, which are focused on the successful detection of local inhomogeneities, contribute to the realization of a positive trend of increasing the efficiency in the process of solving geophysical problems of recognizing the demasking parameters of research objects, primarily in the field of geological exploration. At the same time, rapidly developing, modern experimental methods, techniques and devices, including theoretical developments, have already come close to the successful implementation of not only geophysical problems of deep recognition with a high level of reliability, but also the problems of GPR radar tomography.